2011
DOI: 10.1074/jbc.m111.246876
|View full text |Cite
|
Sign up to set email alerts
|

Common Molecular Determinants of Tarantula Huwentoxin-IV Inhibition of Na+ Channel Voltage Sensors in Domains II and IV

Abstract: The voltage sensors of domains II and IV of sodium channels are important determinants of activation and inactivation, respectively. Animal toxins that alter electrophysiological excitability of muscles and neurons often modify sodium channel activation by selectively interacting with domain II and inactivation by selectively interacting with domain IV. This suggests that there may be substantial differences between the toxinbinding sites in these two important domains. Here we explore the ability of the taran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 36 publications
6
96
0
Order By: Relevance
“…More subtle and primarily subtype-specific reductions in activity were observed with K18A, R26A, K27A, and R29A. Arg 26 , Lys 27 , and Arg 29 are located on loop 4 of HwTX-IV, and our model predicts that some of these amino acids may interact with acidic residues, such as Asp 816 and Glu 818 , located on the DII S3-S4 linker of Nav1.7, that have previously been identified as important for HwTX-IV activity (19). Two of these basic residues (Lys 27 and Arg 29 ) have also been shown to be important for block of VGSCs in rat DRG neurons by the closely related spider toxin, hainantoxin IV (-TheraphotoxinHhn1b) (20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More subtle and primarily subtype-specific reductions in activity were observed with K18A, R26A, K27A, and R29A. Arg 26 , Lys 27 , and Arg 29 are located on loop 4 of HwTX-IV, and our model predicts that some of these amino acids may interact with acidic residues, such as Asp 816 and Glu 818 , located on the DII S3-S4 linker of Nav1.7, that have previously been identified as important for HwTX-IV activity (19). Two of these basic residues (Lys 27 and Arg 29 ) have also been shown to be important for block of VGSCs in rat DRG neurons by the closely related spider toxin, hainantoxin IV (-TheraphotoxinHhn1b) (20).…”
Section: Discussionmentioning
confidence: 99%
“…6b). In addition, our docking model suggests a likely interaction of basic Lys 32 with acidic Glu 811 in Nav1.7 (Glu 837 in Nav1.2), an attractive model given the highly disruptive nature of the K32A and E811Q mutations individually compared with other peptide and channel mutations (19). Interestingly, according to our model, P11A, D14A, L22A, and K18A are located on loops 2 and 3, facing away from the groove formed by the Nav1.7 S1-S2 and S3-S4 loops.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selective Voltage-Sensor Modulation by Biological Toxins used extensive site-directed mutagenesis to show that tarantula toxin HWTX-IV inhibition of central-pore currents critically depends on specific residues in the DII voltagesensor (Xiao et al, 2008;Xiao et al, 2011), suggesting that HWTX-IV indirectly inhibited central-pore currents by blocking movement of a voltage-sensor, and thus preventing activation of the channel. We examined the effects of HWTX-IV on inward gating-pore currents generated by each of the four voltage-sensors and found that HWTX-IV only significantly altered the gating-pore currents generated in DII (Fig.…”
Section: Resultsmentioning
confidence: 99%